The map reader : theories of mapping practice and cartographic representation - Dodge, Martin, 1971-; Kitchin, Rob; Perkins, C. R. (Chichester, West Sussex [England] ; Hoboken, NJ : Wiley-Blackwell, 2011)
Includes bibliographical references and index